Abdominal wound healing: a prospective clinical study. Issue 6083 (6th August 1977) - Irvin, T T; Stoddard, C J; Greaney, M G; Duthie, H L
Abstract : The incidence of wound dehiscence and incisional hernia after two methods of abdominal wound closure (layered closure with retention sutures and single-layer "mass closure") was studied in a randomised prospective clinical trial in a consecutive series of 200 patients. Dehiscence occurred in 1% of patients and herniation in 4-7%; the incidence of these complications was similar with both methods of closure. Seven of the 11 cases of dehiscence or herniation occurred in infected wounds, and wound infection was associated with a tenfold increase in the incidence of these complications. The prevention of wound infection would reduce substantially the incidence of dehiscence and herniation in abdominal wounds.